A apropriação dos espaços públicos pela mulher: o caso dos abrigos de ônibus em Natal-RN - Barros, Gabrielle Marinho de (2015)
Following the thought that the architect and urban planner also has the function to know and understand the people for whom he designs , we propose the challenge of dealing with the idea of handing over public spaces facing a gender approach in Natal/RN. We take in consideration that, throughout history, women did not have the same access as men to the city's spaces and take this evidence to bring the discussion to the contemporary. For this, we talk specifically of bus shelters as an urban part of the city and through interviews, questionnaires and other evaluation methods. All this in an attempt to understand how the woman appropriates public space and if there are differences compared to man.